Education to Reduce Food Waste through Bye Waste Social Business - Elzagi, Verliana; Putra, Edy Yulianto; Febiana, Anjela Rini; Yeronica, Fernanda; Eviyani, Estin Rose; Risvi, Hellena; Melissa, Melissa (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2023)
The issue of food waste is very important as it affects various aspects of human life and the surrounding environment. Business ideas on food waste management are important to help people maintain cleanliness and environmental sustainability. Therefore, an e-booklet business idea with the title "Bye Waste" can be an effective solution for providing such business ideas. The "Bye Waste" e-booklet will contain information on how to manage food waste generated every day. In the e-booklet, it will explain the types of food waste, how to sort and process food waste, and how to use it as organic fertilizer. The "Bye Waste" e-booklet will be sold at an affordable price so that people can easily access it. In order to expand its reach, this e-booklet will be marketed through online platforms such as websites or social media.